The development of ASEAN from historical approach - Keling, Mohamad Faisol; Md Som, Hishamudin; Saludin, Mohamad Nasir; Shuib, Md. Shukri; Ajis, Mohd Na'eim (Canadian Center of Science and Education, 2011)
Since ASEAN was established in 8 August 1967, ASEAN organization was only joined by five countries.Now ASEAN has become a successful regional organization in bringing the attention of the other countries in rest of the world. Generally, ASEAN has successfully nurtures the cooperation in political, economical, social and cultural with establishment in exercise and research facilities for shared interest.Nowadays, ASEAN roles and influence has strong base in Southeast Asia and South Asia regions.ASEAN has taken place as important body in Asia Pacific political stream through Asian Regional Forum (ARF), where it is successful to create attention of various countries not only in Asia region but also United States of America and Europe involvement.Nevertheless, beside the successful story and prosperity achieved by ASEAN at this moment it has uniqueness when it has to face challenges at the early stage of ASEAN establishment. This journal will touch on history and ASEAN life story and explain What and How ASEAN able to strengthen its role and existence at the time Southeast Asia countries need an organization with the ability to unite all the countries in Southeast Asia region.